Mercury Methylating Microbial Community Structure in Boreal Wetlands Explained by Local Physicochemical Conditions - Xu, Jingying; Liem-Nguyen, Van; Buck, Moritz; Bertilsson, Stefan; Björn, Erik; Bravo, Andrea G. (Frontiers in Environmental Science, 2021)
The potent neurotoxic methylmercury (MeHg) is a major concern due to its negative effects on wildlife and human health. Boreal wetlands play a crucial role in Hg cycling on a global scale, and therefore it is crucial to understand the biogeochemical processes involved in MeHg formation in this landscape element. By combining high-throughput hgcA amplicon sequencing with molecular barcoding, we could reveal diverse clades of potential HgII methylators in a wide range of wetland soils. Among Bacteria, Desulfuromonadota (14% of total reads), Desulfurobacterota_A and Desulfurobacterota (up to 6% of total reads), previously classified as Deltaproteobacteria, were important members of the hgcA+ microbial community in the studied wetlands. We also identified Actinobacteriota (9.4% of total reads), Bacteroidota (2% of total reads) and Firmicutes (1.2% of total reads) as members of the hgcA+ microbial community. Within Archaea, Methanosarcinales represented up to 2.5% of the total reads. However, up to half of the hgcA+ community could not be resolved beyond domain Bacteria. Our survey also shows that local physicochemical conditions, such as pH, nutrients concentrations, and water content and prevailing redox states are important for shaping the hgcA+ microbial community structure across the four studied wetlands. Furthermore, we observed a significant correlation between HgII methylation rate constants and the structure of the hgcA+ microbial community. Our findings expand the current knowledge on the the hgcA+ microbial community composition in wetland soils and the physicochemical factors underpinning spatial heterogeneity in such communities.